Organic Agriculture Short-term Courses: Is It a Potential Approach for Well-being and Household Food Supply of Home Gardeners? - Myra Luz M. Homillano (Recent Trends in Arts and Social Studies Vol. 3, 2023)
This chapter determines the feasibility of offering short-term organic agriculture courses at the Central Bicol State University of Agriculture. The United Nations (UN) defines food security as a situation that exists when all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food that meets their dietary needs and food preferences for an active and healthy life. The study employed descriptive, non-experimental research that used a survey instrument. Respondents were required to answer a researcher-made survey questionnaire with items aligned with the problems stated. Results revealed that most prospective enrollees are from the old age bracket (42.25%), interested in home gardening (50.84%), want to learn about basic competencies of organic agriculture (29.05%), and earn a National Certificate for teaching purposes (25.69%). Their main reason for enrolling in the program was health or personal well-being (22.91%). Most respondents wanted to learn about crop and animal production (44.69%) among the learning areas in organic agriculture. Home gardening is gaining popularity in some areas, whether urban or rural, in the country. The potential of home gardens as a food security strategy could lead to its practical adoption, especially for those in the poverty line.